Effects of oxidative treatment techniques on molecular size distribution of humic acids - (:unkn) unknown (I W A PUBLISHING, 2004)
In this study ultrafiltration has been used for the fractionation of humic acid samples. Humic acids were treated in a sequential oxidation system in which ozonation was followed by photocatalytic oxidation using TiO2. Evaluation of the spectroscopic characteristics of the oxidized and fractionated humic acid samples have shown that molecular size distribution ranges shift to lower molecular sizes depending on the oxidation stages. Applied ozone dosage and irradiation time during the photocatalysis stage are the factors affecting the molecular size distribution in the treated humic acid samples. Formation of lower molecular weight compounds during the ozonation stage resulted in increased degradation rates during the photocatalysis stage.
Keywords: humic acid; molecular size distribution; ozonation; photocatalysis; ultrafiltration; DISSOLVED ORGANIC-MATTER; OZONATION; OZONE; NOM